Thoracic Endovascular Aortic Repair for Aberrant Subclavian Artery and Stanford Type B Aortic Intramural Hematoma - Xu, Xia; Wang, Daoquan; Hou, Ningxin; Zhou, Hongmin; Li, Jun; Tian, Liang (Frontiers in Surgery, 2022)
Objectives: To evaluate the in-hospital and later outcomes of thoracic endovascular aortic repair (TEVAR) for type B intramural hematoma (TBIMH) combined with aberrant subclavian artery (aSCA). Methods: From January 2014 to December 2020, 12 patients diagnosed with TBIMH combined with aSCA and treated by TEVAR were enrolled in this retrospective cohort study, including 11 patients with aberrant right subclavian artery and 1 with aberrant left subclavian artery. Handmade fenestrated stent graft or chimney stent or hybrid repair was performed when the proximal landing zone was not enough. Results: The mean age of all the patients was 59.2 ± 7.6 years and 66.7% of patients were men. There were 4 patients with Kommerell's diverticulum (KD). The procedures of all 12 patients were technically successful. There was one case each of postoperative delirium, renal impairment, and type IV endoleak after TEVAR. During follow-up, 1 died of acute pancreatitis 6 months after TEVAR. The overall survival at 1, 3, and 5 years for all 12 patients was 90.9%, 90.9%, and 90.9%, respectively. KD was excluded in 2 patients, and the handmade fenestrated stent graft was applied in the other 2 patients to preserve the blood flow of aSCA. No neurological complications developed and no progression of KD intentionally reserved was observed during follow-up. Conclusion: In conclusion, TEVAR for patients with aSCA and TBIMH was promising. When KD was combined, we could exclude KD or preserve the blood flow of aSCA with regular follow-up for the diverticulum according to the size of KD.